Social and Political Dimensions of Mathematics Education Current Thinking - Jurdak, Murad; Vithal, Renuka; de Freitas, Elizabeth; Gates, Peter; Kollosche, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book examines the current thinking on five critical social and political areas in mathematics education. It focuses on material conditions in teaching and learning, and details features of social life and their influence on mathematics teaching, learning and achievement. Following an introduction, the first section addresses equitable access and participation in quality mathematics education. It explores this issue in different contexts and from different ideological perspectives. The second section traces the emergence and development of the notion of activism in mathematics education in theory, in the literature, in research and in practice. The third section then moves on to explore current research on the political forces at work in identity, subjectivity and (dis)ability within mathematics education, showing how emphasis on language and discourse provides information for this research, and how new directions are being pursued to address the diverse material conditions that shape learning experiences in mathematics education. Economic factors behind mathematics achievement form the topic of section four, which examines the political dimensions of mathematics education through the influence of national and global economic structures. The final section addresses distribution of power and cultural regimes of truth, based on the premise that although often deemed apolitical, mathematics and mathematics education are highly political institutions in our society. The book concludes with a summary and recommendations for the future.
1. Introduction -- 2. Survey of the Social and Political Dimensions of Mathematics Education -- 3. Summary and Looking Ahead.
Keywords: Education; Educational policy; ducation and state; Mathematics -- Study and teaching; Educational sociology; Education and sociology; Sociology, Educational; Education; Mathematics Education; Sociology of Education; Educational Policy and Politics; Electronic books